Agenesis of the internal carotid artery associated with neurofibromatosis type II. - Chen, M C; Liu, H M; Huang, K M (American Journal of Neuroradiology, 1994)
We report a case of agenesis of the internal carotid artery associated with neurofibromatosis type II. Common carotid arteriograms showed no visualization of the internal carotid artery. CT revealed absence of the corresponding carotid canal. MR documented absence of the internal carotid artery in the cavernous sinus.